Pengaruh Kepemimpinan Transformasional Kepala Sekolah terhadap Pengembangan Profesionalisme Guru di SMP Swasta Muhammadiyah 01 Medan - Syafira Syafira; Candra Wijaya; Khairuddin Khairuddin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study is to find out the most important effect of transformational leadership on teacher professionalism. Development at SMP Swasta Muhammadiyah 01 Medan. This study method is a quantitative study survey research type. 60 teachers participated in this study. Principals and teachers were used as examples. The research instrument was a questionnaire. Dat collection instruments with questionnaires and data analysis techniques with normality test, linearity test and homogeneity test and hypothesis testing (using t-test). The result of this study show that there is a positive and significant effect between the main variable and teacher professionalism ini Muhammadiyah 01 Medan Private High School. This is eviident form the result of the hypothesis testing, which shows that the main transformational leadership contributes 0.388 X 100% = 38.8% to teacher professionalism. The t-test performed gave a tnumber = 3.870 whilw the ttabel value = 2.042. Since tnumber (3.870) > ttabel (2.042), it showsjthat there is a positive and significant effect in the form of a linear and predictive relationship between the main variable and professionalism of teachers in SMP Swasta Muhammadiyah 01 Medan. Regression line Ŷ = 46.654 + 0.322 X.